Study on the Prediction of Residual Life of Concrete Rectangular Beams after Fire - Zhongqiang Wang; Guan Huang; Yaodong Wang (Advances in Materials Science and Engineering)
To study concrete members’ safety and residual life after fire damage, this study takes concrete beams as the research object. Then, it predicts the residual energy of concrete beams after fire by investigating their temperature field after the fire and deriving the required data for studying the corresponding residual life. This study first establishes the temperature field model of concrete beams under fire by using the finite element software ABAQUS, selects the ISO-834 standard warming curve as the fire condition, and obtains the thermodynamic parameters and calculation formulas of concrete and steel reinforcement from a large number of experiments and examples, to provide reliable materials for the temperature field simulation, reliability analysis, and residual life prediction by using the finite element software ABAQUS afterward. The results obtained from the temperature field simulation are used to calculate the probability of failure using the Monte Carlo method calculation program prepared by MATLAB software in conjunction with the equation of limit state to derive the results of the residual life of the concrete member. When the concrete beam with a definite strength of C40 and a thickness of the protective layer of 35 mm undergoes a fire for 2 hours, the residual life of the concrete beam is 13 years and 7 years, respectively, under the requirements of the general building and the use of the essential building components. They are about 13 years and 7 years, respectively. To verify the reasonableness of the derived equations, confirmed cases are used to demonstrate the feasibility. Finally, by analyzing the results of reliability and remaining life under different working conditions, it can be concluded that the concrete grade and the thickness of the concrete protective layer have a significant effect on the remaining life of concrete beams after the fire, regardless of the requirements of general or essential building components.